Judges in contemporary democracy : an international conversation - Breyer, Stephen G., 1938-; Badinter, Robert (NYU Press, 2004)
Law, politics, and society in the modern West have been marked by the increasing power of the judge: the development of constitutional justice, the evolution of international judiciaries, and judicial systems that extend even further into social life. Judges make decisions that not only enforce the law, but also codify the values of our times. In the summer of 2000, an esteemed group of judges and legal scholars met in Provence, France, to consider the role of the judge in modern society. They included Robert Badinter, former president of the Constitutional Council in France; Stephen Breyer, J.